Composition dependence of ferroelectric properties in (111)-oriented epitaxial HfO2-CeO2 solid solution films. (1st November 2022) - Hirai, Koji; Shiraishi, Takahisa; Yamaoka, Wakiko; Tsurumaru, Risako; Inoue, Yukari; Funakubo, Hiroshi
Abstract: The composition dependence of ferroelectric properties was investigated for (111)-oriented epitaxial HfO2 -CeO2 solid solution films. Twenty nanometer thick films with different compositions were prepared on (111)ITO//(111)YSZ substrates at room temperature by pulsed laser deposition and subsequent heat treatment at 1000 °C under atmospheric N2 or O2 gas flow. All the films had fluorite structures, and their crystal symmetries changed from monoclinic through orthorhombic to tetragonal/cubic phases as x increased for the (Hf1− x Ce x )O2 ( x = 0.12–0.25) films. The orthorhombic phase was confirmed by X-ray diffraction analysis for films with x  = 0.15 and 0.17. On the other hand, ferroelectric properties were observed in films with x  = 0.15–0.20, suggesting that a field-induced phase transition takes place for films with x  = 0.20. The film composition showing ferroelectricity was the widest range of doping concentration for reported epitaxial HfO2 -based films. Their remanent polarization ( P r ) and coercive field ( E c ) were almost identical, at 17–19 μ C cm −2 and 2.0–3.0 MV cm −1 . This wide ferroelectric composition range with relatively similar ferroelectricity is due to the solid solution of the same fluorite structure of HfO2 and CeO2 with monoclinic and cubic symmetries, that are respectively lower and higher crystal symmetries of the ferroelectric orthorhombic phase.